Fertility Characteristics Of Daughter Cows Of Different Selections Of The Holshtin Breed (Eurasian Research Bulletin, 2023)
In the article, the parameters such as duration of estrus duration and coefficient of variation of the daughters of Holstein cows imported from abroad, obtained from cows of different selections, in the warm climate conditions, and the offsprings obtained from cows belonging to the selection of the USA, Austria and Germany, such as changes in physiological norms indicators are given.